The Effect Of Utilization Of Mysql On The Results Of Student Learning In Subject Of Data Basis - Supari Muslim; Didik Triaswira; Erina Rahmadyanti; Soeparno Soeparno; Nita Kusumawati (Journal of Educational Science and Technology (EST), 2019)
This study aims to determine: (1) differences in learning activities between students who use MySQL and students who use Ms. Access on subjects in Database Processing with basic competencies in understanding language in class XI of the RPL Department of SMK 2 Surabaya; (2) differences in learning outcomes between students who use MySQL and students using Ms. Access on Database subjects with basic competencies in understanding language in class XI of the RPL Department of SMK 2 Surabaya.The research design used was a "non -equivalent control group design" design which involved two classes, namely XI RPL1as an experimental class with a total sample of 33 students and class XI RPL-2 as a control class with a total sample of 34 students. The place of research was conducted at SMK Negeri 2 Surabaya. The study found that: (1) learning activities for students who studied using MySQL applications were significantly higher than the learning activities of students who studied using Ms. Access; and (2) learning outcomes for students who learn using MySQL applications are significantly higher than the learning outcomes of students who study using Ms. Access.